Cu nanoparticle-decorated two-dimensional carbon nanosheets with superior photothermal conversion efficiency of 65 % for highly efficient disinfection under near-infrared light. (10th October 2021) - Song, Jie; Li, Jun; Bai, Xiangren; Kang, Liang; Ma, Liying; Zhao, Naiqin; Wu, Shuilin; Xue, Yuan; Li, Jiajun; Ji, Xiaojian; Sha, Junwei
Graphical abstract: Highlights: Strong NIR absorption of 2D C and LSPR feature of Cu NPs co-enhance photothermy. 2D C/Cu2 exhibits a remarkable photothermal conversion efficiency of 65.05 %. Synergetic effect of photothermy and ion release can effectively sterilize. 2D C/Cu shows broad-spectrum bactericidal activity without apparent toxicity. Abstract: Low photothermal conversion efficiency restricts the antibacterial application of photothermal materials. In this work, two-dimensional carbon nanosheets (2D C) were prepared and decorated with Cu nanoparticles (2D C/Cu) by using a simple soluble salt template method combined with ultrasonic exfoliation. The photothermal conversion efficiency of 2D C/Cu system can be optimized by changing the content of Cu nanoparticles, where the 2D C/Cu2 showed the best photothermal conversion efficiency ( η ) of 65.05 % under 808 nm near-infrared light irradiation. In addition, the photothermal performance can affect the release behavior of Cu ions. This superior photothermal property combined with released Cu ions can endow this 2D hybrid material with highly efficient antibacterial efficacy of 99.97 % ± 0.01 %, 99.96 % ± 0.01 %, 99.97 % ± 0.01 % against Escherichia coli, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus, respectively, because of the synergetic effect of photothermy and ion release. In addition, this 2D hybrid system exhibited good cytocompatibility. Hence, this study provides a novel strategy to enhance the photothermal performance of 2D materials and thus will be beneficial for development of antibiotics-free antibacterial materials with safe and highly efficient bactericidal activity.